Dietary Quality Assessed by the HEI-2010 and Biomarkers of Cardiometabolic Disease: An Exploratory Analysis. (3rd October 2019) - Crowe-White, Kristi M.; Ellis, Amy C.; Mehta, Tapan; Locher, Julie L.; Ard, Jamy D.
Abstract: Objectives: This study explores relationships between cardiometabolic measures of antioxidant capacity or inflammation and diet quality assessed by the Healthy Eating Index (HEI)-2010 which measures conformity to Dietary Guidelines for Americans. This cross-sectional study was an ancillary analysis of baseline data for a randomized controlled trial with older adults at risk for cardiometabolic disease (ClinicalTrials.gov #NCT00955903). Methods: Community-dwelling older adults (n = 133, 49% male, 70.4 ± 4.8 years) with a body mass index of 30–40 kg/m 2 provided a fasted blood sample for measurement of antioxidant capacity, high-sensitivity C-reactive protein, tumor necrosis factor-alpha, and interleukin-6. Dietary data were generated from the mean of three 24-hour recalls. Results: After adjustment for potential confounders, HEI-2010 composite scores were not significantly associated with decreased inflammation or greater antioxidant capacity. In analysis of the 12 components composing the HEI-2010, significant positive association was observed between total dairy and total serum antioxidant capacity (0.043; 95% CI, 0.008–0.069). Significant associations observed in inflammatory markers were between total vegetable and tumor necrosis factor-alpha (−0.078; 95% CI, −0.151 to −0.005), sodium and interleukin-6 (0.091; 95% CI, 0.023–0.158), and scores for combined calories from solid fats, alcoholic beverages, and added sugars and interleukin-6 (0.139; 95% CI, 0.027–0.252). In models adjusting for HEI-2010 composite score when significant associations were observed between component scores and biomarkers, two of six associations were strengthened by adding the composite score as a potential confounder. Conclusions: Largely null findings along with those inconsistent with scientific expectations suggest caution in extrapolating adherence to the HEI-2010 with an individual's inflammatory or antioxidant status. Results merit additional investigation with other biomarkers of chronic disease and emphasis on dietary patterns given potential synergy within food combinations.